Correction: Complete Revascularization and Survival in STEMI - Miha Sustersic; Miha Mrak; Polona Svegl; Anamarija Rebolj Kodre; Igor Kranjec; Zlatko Fras; Matjaz Bunc (Ubiquity Press, 2021)
This article details a correction to: Sustersic M, Mrak M, Svegl P, Kodre AR, Kranjec I, Fras Z, et al. Complete Revascularization and Survival in STEMI. 'Global Heart'. 2021; 16(1): 64. DOI: http://doi.org/10.5334/gh.1040